Ibnu Khaldun's Constructivism in Islamic Religious Education: Case Study at the FAI Masters at Singaperbangsa University Karawang - Ferianto, Ferianto; Makbul, M; Firmansyah, Firmansyah (Al-Hayat: Journal of Islamic Education, 2024)
Ibn Khaldun's works, such as al-Muqaddimah, contain elements that can be linked to the principles of constructivism. In Islamic education, constructivism can be interpreted as an approach that values students' active role in constructing their knowledge. This research aims to analyze Ibn Khaldun's constructivist thinking in the context of Islamic religious education. This research uses a qualitative approach with a case study type, focusing on a particular case to be observed and analyzed carefully until complete. The data source this time was carried out at Singaperbangsa University Karawang in the Islamic Education Masters study program. Data collection using interviews, observation and documentation techniques. The data analysis technique follows the Miles and Huberman analysis flow, including data reduction, data presentation, and drawing conclusions or verification. The research results show that according to Ibnu Khaldun, constructivism in education can be carried out through social relationships in building (constructing) students' understanding. By providing freedom in determining lecture contracts, determining groups in building an understanding of the material to be presented, and determining references or referents based on case studies for problem-solving, educators provide space and time for discussion. So that students can reflect on their experiences and build an understanding of the world in which they live. This research is limited to the thoughts of figures from an Islamic education perspective. The findings of this research are relevant to Ibn Khaldun's constructivist thinking, which states that building a person's understanding can be done through social interaction with the environment and people around him.